2014
DOI: 10.11648/j.ajls.20140205.12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen and Phosphorus Fertilizer Levels on Growth and Development of Barley (Hordeum vulgare L.) at Bore District, Southern Oromia, Ethiopia

Abstract: Fertilizer requirement of crops vary from location to location owing to several factors. Thus there is a need to determine site specific fertilizer recommendation for specific crops. Accordingly, an experiment was conducted on the effects of different nitrogen and phosphorus fertilizer levels on yield and yield components of barley at south eastern Oromia, Bore, in 2009 cropping season. The barley variety Biftu was used as test crop. It is a newly released variety from Sinana Agricultural Research Center. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 8 publications
10
18
0
Order By: Relevance
“…Lack of increasing trend between blended NPSB and interaction effects of blended NPSB and nitrogen fertilizer rates could be attributed to the counteracting effects of phosphorus nutrient on N nutrient effects because N tends to increase vegetative growth, while phosphorus hastens the reproductive growth. This is in conformity with finding of Tigre et al (2014), who reported that under no phosphorus application, days to heading showed an increasing tendency with rising N rates on barley (Hordeum vulgare L.).…”
Section: Days To Headingsupporting
confidence: 93%
“…Lack of increasing trend between blended NPSB and interaction effects of blended NPSB and nitrogen fertilizer rates could be attributed to the counteracting effects of phosphorus nutrient on N nutrient effects because N tends to increase vegetative growth, while phosphorus hastens the reproductive growth. This is in conformity with finding of Tigre et al (2014), who reported that under no phosphorus application, days to heading showed an increasing tendency with rising N rates on barley (Hordeum vulgare L.).…”
Section: Days To Headingsupporting
confidence: 93%
“…Previous studies have reported urea N fertilizer effects on stem diameter, leaf area index and biomass yield of barley components, in which the prominent feature was the increase of biomass yield with increasing urea N supply (Baethgen et al 1995;Hansen et al 2002;Cantero-Martínez et al 2003;McKenzie et al 2005). Tigre et al (2014) found that the mature stage of barley growth lasted 3-8 days longer with increasing urea N fertilization rates from 30 to 120 kg/ha. Similarly, maturity was observed to last 5-11 days longer of for highland barley in the present study, suggesting that urea N fertilization promoted vegetative growth and delayed maturity.…”
Section: Influence Of Urea Nitrogen Fertilization On Highland Barley mentioning
confidence: 89%
“…Cantero et al, (1995), Le Gouis et al, (1999) and Oweis et al, (1999) observed similar results for grains spike-1 in barley was significantly increased with increasing N fertilization as reported by Moselhy & Zahran (2002). They further revealed that application of nitrogen fertilizer significantly increased spike length, number of grains spike-1, 1000 grain weight, grain yield and N uptake by the crop (Chaudhary & Mehmood, 1998;Bakhsh et al, 1999;Wakene et al, 2014;Tilahun et al, 2000) Both N and P significantly influenced total biomass but their interaction effect was not significant ( Table 1). The highest TBM of 3.9 t ha-1 was recorded in the treatment which received 69/30 NP kg N ha-1 though not significantly different to the TBM obtained from 0/0NP Kg N ha-1 (2.4 t ha-1) ( Table 1).…”
Section: Effects Of Nitrogen and Phosphorus Fertilizer Rates On Plantmentioning
confidence: 99%